2012
DOI: 10.4314/njp.v39i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypoglycaemia in under-five children presenting with acute diarrhoea in University of Calabar Teaching Hospital, Calabar.

et al.

Abstract: Background: The clinical features of hypoglycaemia and severe dehydration are similar, and these two can occur in a child presenting with acute diarrhoea. Hypoglycaemia occurring in a growing brain is deleterious and must be detected and treated. Objective: To determine the prevalence of hypoglycaemia among under-five children presenting with acute diarrhoea in UCTH, Calabar. Method: This was a prospective study of 150 children aged six weeks to five years presenting with acute diarrhoea in UCTH, Calabar from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 6 publications
0
16
1
Order By: Relevance
“…12 All previous Nigerian studies on this subject were conducted in tertiary-healthcare hospitals and none in secondaryhealthcare hospital, yet a significant number of children are cared for in secondary-healthcare facilities. 7 Considering that in developing countries, childhood diarrhoea itself is grossly under-reported and its incidence underestimated, 13 the magnitude of the paucity of information on hypoglycaemia coexisting with diarrhoea becomes more obvious. At present, in Nigeria, the extent to which hypoglycaemia occur in children with diarrhoea is uncertain.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…12 All previous Nigerian studies on this subject were conducted in tertiary-healthcare hospitals and none in secondaryhealthcare hospital, yet a significant number of children are cared for in secondary-healthcare facilities. 7 Considering that in developing countries, childhood diarrhoea itself is grossly under-reported and its incidence underestimated, 13 the magnitude of the paucity of information on hypoglycaemia coexisting with diarrhoea becomes more obvious. At present, in Nigeria, the extent to which hypoglycaemia occur in children with diarrhoea is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…4,6 In a study in Calabar, Nigeria, 4.0% of under-five children presenting with acute diarrhoea were found to have hypoglycaemia. 7 A study in a rural district hospital in Kenya, reported a prevalence of hypoglycaemia as high as 23.3% among children with acute diarrhoea at the point of hospital admission. 12 All previous Nigerian studies on this subject were conducted in tertiary-healthcare hospitals and none in secondaryhealthcare hospital, yet a significant number of children are cared for in secondary-healthcare facilities.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations